Adverse Childhood Experiences (ACEs) and Alcohol Abuse among South Carolina Adults. (7th June 2018) - Crouch, Elizabeth; Radcliff, Elizabeth; Strompolis, Melissa; Wilson, Abygail
ABSTRACT: Background : Adverse childhood experiences (ACEs) have been associated with negative adult health outcomes, including alcohol misuse. The impact of ACEs on alcohol use may vary by gender, with ACEs impacting women more than men in coping with adulthood stressors. Objectives : The objective of this study is to examine the gender-specific relationships between ACEs and self-reported binge drinking and heavy drinking in adulthood among South Carolina residents. Methods : This study analyzed a sample of 8492 respondents who completed the 2014 or 2015 South Carolina Behavioral Risk Factor Surveillance System (BRFSS) survey. Logistic regression was used to examine the impact of types and the number of ACEs on binge drinking and heaving drinking in adulthood. Results : Thirty-seven percent of men and 22.8% of women survey respondents reported binge drinking and 12.2% of men and 4.1% of women reported heavy drinking. Almost all categories of ACE were associated with increased odds of reporting binge and heavy drinking; household mental illness had the greatest odds for men (aOR 1.31, 95% CI 1.30–1.33) and emotional abuse had the greatest odds for women (aOR 1.42, 95% CI 1.40–1.43). Men and women with four or more ACEs had greater odds of reporting binge and heavy drinking compared to their counterparts. Conclusions/Importance : Given the potential for negative outcomes associated with alcohol misuse and transmission of risky alcohol-related behaviors from parent to child, strategies that utilize a multigenerational approach could have a large impact on population health.